Circulating substance P levels and shoulder joint contracture after arthroscopic repair of the rotator cuff. Issue 9 (28th February 2008) - Franceschi, F; Longo, U G; Ruzzini, L; Morini, S; Battistoni, F; Dicuonzo, G; Maffulli, N; Denaro, V
Abstract : Objective: To determine the plasma levels of substance P (SP) in patients with postoperative stiffness after arthroscopic rotator cuff repair. Design: Plasma samples were obtained at 15 months from surgery from two groups of patients who underwent arthroscopic repair of a rotator cuff tear. In group 1, 30 subjects (14 men, 16 women; mean age 64.6 years, range 47 to 78) with shoulder stiffness 15 months after arthroscopic rotator cuff repair were recruited. In group 2, 30 patients (11 men, 19 women; mean age 57.8 years, range 45 to 77) were evaluated 15 months after successful arthroscopic rotator cuff repair. Immunoassays were performed with commercially available assay kits to measure the plasma levels of SP. Results: Plasma levels of SP in patients with postoperative stiffness were significantly greater than those in the control group (mean 81.06 (SD 27.76) versus 23.49 (5.64), p<0.05). Conclusions: The plasma concentrations of substance P in patients with shoulder stiffness after arthroscopic rotator cuff repair are higher compared with plasma levels of SP in patients with a good postoperative outcome. The neuronal upregulation of SP shown in the plasma of patients with postoperative shoulder stiffness may underlie not only the symptoms but also its development of adhesive capsulitis.